A baseline assessment of farm, household, gender and socioeconomic attributes in Bangladesh - Mishra, Ashok K.; Dela Rueda, Justin B.; Villanueva, Donald B.; Raviz, Jeny V.; Pede, Valerien O. (CGIAR Initiative on Asian Mega-Deltas, 2024)
"Launched in June 2022, the CGIAR Initiative on Securing the Food Systems of the Asian Mega-Deltas for Climate and Livelihood Resilience or the AMD Initiative forged partnerships with various stakeholders in the most threatened delta regions – the Ganges-Brahmaputra-Meghna (GBM) Delta, Irrawaddy Delta, and Mekong Delta. Several food systems innovations were co-developed and scaled with partners to enable resilient, inclusive, and productive deltas while maintaining socio-ecological integrity. To achieve these objectives using a holistic approach, the AMD operates within five work packages that tackle various food system components such as farming systems, nutrition and health, climate information, governance and development planning.